Preferensi Mahasiswa dalam Meningkatkan Human Capital Melalui Program Pascasarjana - Muhardi Muhardi; Sundaya Sundaya (Universitas Islam Indonesia, 2006)
This paper described any factors that influential probability college student’s to studying in pascasarjana program’s. Further, there are behaviour’s analysis specifically both college student’s who are to become a member of campus organization and college student’s who are not to become a member of campus organization. To achieve its, we use linear probability model (probit). Estimation result’s are first, its probability significantly determined by age, number they younger brother and sister, and then by estimate of gross benefit from earning after they work with master title’s. Second, probability college student’s who are to become a member of campus organization to studying in pascasarjana program’s exceed probability college student’s who are not to become a member of campus organization.Keyword: graduate program, human capital, probit model